BUDAYA PENGELOLAAN KELAS SEBAGAI PILAR UTAMA UNTUK MENDUKUNG KEBERHASILAN PENDIDIKA KARAKTER ISLAMI PESERTA DIDIK: (STUDI PENELITIAN MTS NURUL FALAH KOTA TASIKMALAYA) - Nitalia Fitriani; Wildan, Asep (HASBUNA : Jurnal Pendidikan Islam, 2025)
Classroom management culture plays an important role in supporting the success of Islamic character education for students. This study is based on the reality in the field that classroom management by some teachers is still conventional and does not fully reflect Islamic values. This study aims to describe the form of classroom management culture at MTs Nurul Falah Tasikmalaya, analyze its influence on Islamic character education for students, and identify the challenges faced in its implementation. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the classroom management carried out has integrated Islamic values such as discipline, responsibility, and mutual respect, which have a positive impact on the formation of student character. However, challenges are still found, especially in terms of limited teacher understanding and less than optimal training related to Islamic-based classroom management.